2021
DOI: 10.1101/2021.03.26.21254259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hemodialysis Patients Show a Highly Diminished Antibody Response after COVID-19 mRNA Vaccination Compared to Healthy Controls

Abstract: 1. Abstract 1.1 Background and Objectives Hemodialysis patients are prone to infection with SARS-COV2 and show a high probability of a severe course of disease and high mortality when infected. In many countries hemodialysis patients are prioritised in vaccination programs to protect this vulnerable community. However, no hemodialysis patients were included in efficacy trials of SARS CoV-2 vaccines and therefore efficacy and safety data for this patient group are lacking. These data would be critical, since he… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 24 publications
6
31
2
Order By: Relevance
“…Our study has several limitations. While we have a reasonable sample size (81 dialysis patients), which is similar or even larger compared to several other studies (12,13,25), our control group is not age-and gender-matched. In addition, we evaluated only one of the currently approved SARS-CoV-2 vaccines with samples from a single dialysis center and did not perform in-depth immune phenotyping or assessment of SARS-CoV-2 responsive T-cell frequencies.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our study has several limitations. While we have a reasonable sample size (81 dialysis patients), which is similar or even larger compared to several other studies (12,13,25), our control group is not age-and gender-matched. In addition, we evaluated only one of the currently approved SARS-CoV-2 vaccines with samples from a single dialysis center and did not perform in-depth immune phenotyping or assessment of SARS-CoV-2 responsive T-cell frequencies.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, we found no significant differences in vaccination-induced IgA levels in both saliva and plasma between our study groups. Although several studies reported lower protective IgG titers over time following hepatitis B, influenza A or SARS-CoV-2 vaccinations, IgA levels were not analyzed here (9)(10)(11)(12)(13)(14)(15)(16)(17). Interestingly, a monoclonal IgA antibody capable of recognizing both the SARS-CoV-1 and SARS-CoV-2 spike proteins and blocking ACE2 receptor interaction combined with an increased neutralization ability over its IgG equivalent has been described (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several small studies investigating the role of COVID-19 vaccines in dialysis patients have been reported recently and are summarized in Table 2 [ 8 , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] ]. The development of anti-SARS-CoV-2 antibodies is variable and depends on several factors, including the time from vaccine administration to antibody measurement, and the type of antibody assay.…”
Section: Methodsmentioning
confidence: 99%
“…2 Although the nephrology community has called for ESKD patients to have priority for vaccination as a vulnerable population, there has been an underlying concern that these patients may not mount a good response to vaccination or even after a previous infection with SARS-CoV-2. In this issue of Kidney International, we present the initial experience of nephrologists from around the world regarding the immunogenicity of prior coronavirus disease 2019 (COVID- 19) infection and the response to the COVID-19 vaccines among patients with ESKD receiving kidney replacement therapy (Table 1 [3][4][5][6][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%